New genome assembly of the barn owl (Tyto alba alba). Issue 5 (19th February 2020) - Ducrest, Anne‐Lyse; Neuenschwander, Samuel; Schmid‐Siegert, Emanuel; Pagni, Marco; Train, Clément; Dylus, David; Nevers, Yannis; Warwick Vesztrocy, Alex; San‐Jose, Luis M.; Dupasquier, Mélanie; Dessimoz, Christophe; Xenarios, Ioannis; et al.
Abstract: New genomic tools open doors to study ecology, evolution, and population genomics of wild animals. For the Barn owl species complex, a cosmopolitan nocturnal raptor, a very fragmented draft genome was assembled for the American species ( Tyto furcata pratincola ) (Jarvis et al. 2014). To improve the genome, we assembled de novo Illumina and Pacific Biosciences (PacBio) long reads sequences of its European counterpart ( Tyto alba alba ). This genome assembly of 1.219 Gbp comprises 21, 509 scaffolds and results in a N50 of 4, 615, 526 bp. BUSCO (Universal Single‐Copy Orthologs) analysis revealed an assembly completeness of 94.8% with only 1.8% of the genes missing out of 4, 915 avian orthologs searched, a proportion similar to that found in the genomes of the zebra finch ( Taeniopygia guttata ) or the collared flycatcher ( Ficedula albicollis ). By mapping the reads of the female American barn owl to the male European barn owl reads, we detected several structural variants and identified 70 Mbp of the Z chromosome. The barn owl scaffolds were further mapped to the chromosomes of the zebra finch. In addition, the completeness of the European barn owl genome is demonstrated with 94 of 128 proteins missing in the chicken genome retrieved in the European barn owl transcripts. This improved genome will help future barn owl population genomic investigations. Abstract : We assemble the genome of the European barn owl ( Tyto alba alba ) of 1.219 Gbp by mixing Illumina (117×) and Pacific Biosciences (PacBio) long reads (12×) technologies. BUSCO (Universal Single‐Copy Orthologs) analysis revealed an assembly completeness of 94.8% with only 1.8% of the genes missing out of 4, 915 avian orthologs searched, a proportion similar to that found in the genomes of the zebra finch ( Taeniopygia guttata ) or the collared flycatcher ( Ficedula albicollis ). In addition, we identify the Z chromosome' scaffolds, 73% of proteins thought to be missing in the chicken.